2009
DOI: 10.1002/jcla.20346
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 rs1801157 polymorphism in patients with breast cancer, hodgkin's lymphoma, and non‐hodgkin's lymphoma

Abstract: Chemokines and their receptors regulate the trafficking of immune cells during their development, inflammation, and tissue repair. The single-nucleotide polymorphism (SNP) rs1801157 (previously known as CXCL12-A/ stromal cell-derived factor-1 (SDF1)-3'A) in CXCL12/SDF1 gene was assessed in breast cancer, Hodgkin's lymphoma (HL), and non-Hodgkin's lymphoma (NHL), since the chemokine CXCL12, previously known as SDF1, and its receptor CXCR4 regulate leukocyte trafficking and many essential biological processes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Inflammation sustains the proliferation of cancer cells by stromal cells activation and chemokines secretion. Some chemokines, such as CXCL12 and CXCL13, have proven roles in the pathogenesis of lymphoma [47,48].…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation sustains the proliferation of cancer cells by stromal cells activation and chemokines secretion. Some chemokines, such as CXCL12 and CXCL13, have proven roles in the pathogenesis of lymphoma [47,48].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Association of these polymorphisms to cancer has been previously reported by many investigators [De Oliveira KB et al, 2009;Rabkin CS et al, 1999].…”
Section: Discussionmentioning
confidence: 78%
“…Whereas, they didn't find any significant differences in genotypes distributions with breast cancer and Hodgkin's lymphoma [De Oliveira KB et al, 2009].…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have examined the association between disease susceptibility and the CXCL12-G801A polymorphism (27)(28)(29)(30)(31)(32)(33). These studies indicated that the CXCL12-G801A polymorphism was associated with an increased risk of HIV infection, lung cancer, breast cancer, acute leukemia, prostate cancer, non-Hodgkin's lymphoma and oral squamous cell carcinoma (27)(28)(29)(30)(31)(32)(33)(34). However, only a small number of studies focused on the presence of the CXCL12-G801A polymorphism in CRC patients to clarify whether the CXCL12-G801A polymorphism is associated with disease susceptibility and clinical characteristics in CRC (31,35).…”
Section: Discussionmentioning
confidence: 99%